2017
DOI: 10.1515/ijm-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

Management educators in practice: to be critical or not to be critical, that is the question

Abstract: The field of management education has been the focus of much debate in recent times regarding the relevancy of its content and process. How we define relevance has implications for all stakeholders of management. As a result, how applicable are the alternative approaches to management education such as critical management education (CME). This research explores how criticality is perceived, experienced, and translated into the everyday practices of critical management educators. The research found that there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The most relevant work recently has been that of Breen (2012). Breen’s research identified that criticality is expressed differently according to the seniority and gender of the educators who identify as CME academics in Ireland and the United Kingdom.…”
Section: Cme’s Middle Agementioning
confidence: 99%
“…The most relevant work recently has been that of Breen (2012). Breen’s research identified that criticality is expressed differently according to the seniority and gender of the educators who identify as CME academics in Ireland and the United Kingdom.…”
Section: Cme’s Middle Agementioning
confidence: 99%